Coccidioidomycosis (Valley Fever) Case Data for the Southwestern United States. (22nd April 2020) - Gorris, Morgan E.; Cat, Linh Anh; Matlock, Melissa; Ogunseitan, Oladele A.; Treseder, Kathleen K.; Randerson, James T.; Zender, Charles S.
We compiled a coccidioidomycosis (Valley fever) case database for three states in the southwestern United States (US). Currently, county-level, monthly case counts are available from 2000–2015 for Arizona, California, and Nevada. We collected these data from each respective state public health agency. The Valley fever case database is available on GitHub, athttps://github.com/valleyfever/valleyfevercasedata . This database may be used to examine relationships between the number of Valley fever cases and hypothesized explanatory variables such as environmental conditions, social determinants, human behavior, occupational activities, public policies, or other risk factors. We aim to provide regular updates to this database and include more states as data become available.